Demographic and geographic determinants of regional physician supply - Michael Kuhn; Carsten Ochsen (Universität Rostock, Institut für Volkswirtschaftslehre, 2009)
Against the backdrop of an ongoing debate in most countries about the geographic (mal-)distribution of physician practices, we develop a theoretical and empirical framework to analyze how physician supply at regional level depends on demographic (population size, age structure, fertility and migration) and geographic determinants. Particular attention is given (i) to local population change as a predictor of future demand for physician services, (ii) to the way in which the age-structure of the (potential patient) population and regional structure interact in shaping the profitability of treating the local population, and (iii) to cross-regional correlations in physician supply. Using regional data for Germany, we examine econometrically the determinants of regional physician supply. We find it to be negatively related to both the population share 60+ and the population share 20- in rural areas. While both population shares tend to have a less negative impact in urban areas, a pronounced positive effect arises only for the share 20- in regions with agglomeration character. Net migration and natural balance turn out to be significant positive as long-run determinants only, indicating thus their role as predictors of future demand. On average, cross-regional spillovers in demand do not seem to be important determinants of regional supply.
Keywords: I11; J44; J10; R23; C33; C31; 330; age structure; physician supply; regional population ageing; regional migration; overlapping generations; panel data; spatial model; Ärzte; Gesundheitsvorsorge; Räumliche Verteilung; Alternde Bevölkerung; Regionale Bevölkerungsentwicklung